FAKTOR DETERMINAN MINAT PEGAWAI STAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG TERHADAP BANK KONVENSIONAL - Lestari, Novi (STUDIA: JURNAL HASIL PENELITIAN MAHASISWA, 2016)
Background elections this theme is because although it has opened the Department of Syariah and Islamic Economics Islamic Banking Studies Program. STAIN Syaikh Abdurrahman Siddik Bangka Belitung still choose conventional bank as a partner in conducting transactions in the campus environment. On the pretext that the STAIN Syaikh Abdurrahman Siddik Bangka Belitung Islamic college is owned by the government under the auspices of the Ministry of Religious Affairs of the Republic of Indonesia, where the government generally use the services of conventional banks. This research was conducted in order to determine STAIN employee interest in using the services of conventional banks in STAIN Syaikh Abdurrahman Siddik Bangka Belitung and the factors that affect that interest. This research is a field research with quantitative research methods. Methods of data analysis used in this study is the instrument test questions using validity and reliability test, classic assumption test in the form of normality test, multicollinearity, autocorrelation and heteroscedasticity test, test data variables with multiple linear regression analysis and hypothesis testing with a partial test ( T test), simultaneous test (F test) and the coefficient of determination (R2 test). From the research, the result that the interest of employees in using the services of conventional banks in STAIN SAS BABEL is very low. Based on the results of the test instrument known questions that test the validity of all the items is a valid question and test the reliability of all the variables is reliable. Classical assumption test in the regression model in this study as a whole has been qualified with excellent classical assumptions. Based on the test data variables and test hypotheses known that factors location access bank and promotional factors have positive influence and significant to the interests of employees and the central MOU factors also have a significant influence but does not give a positive effect, because the regression coefficient is negative. While factors excellent service and facilities factors have positive influence on the interests of employees, but it does not have significant influence.